Non-union treatment based on the "diamond concept" is a clinically effective and safe treatment option in older adults - Tanner, Michael Christopher; Hagelskamp, Saskia; Vlachopoulos, Wasilios; Miska, Matthias; Findeisen, Sebastian; Grimm, Andreas; Schmidmaier, Gerhard; Haubruck, Patrick (Clinical interventions in aging, 2020)
Background: Patients >60 years suffering from non-unions are often unable to perform activities of daily living and often become dependent on nursing care. Evidence regarding treatment options and outcome is nonexistent. This study sought to determine the clinical effectiveness and safety of one- or two-step non-union therapy in elderly patients. Methods: This study was a single-site retrospective database analysis of older adults with long bone non-unions treated via "diamond concept". All medical records of patients receiving surgical treatment of non-unions between 01/01/2010 and 31/12/2016 were reviewed. Clinical and radiological outcome subsequent to non-union therapy were evaluated. Results: A total of 76 patients (37 patients were treated with one-step and 39 patients with Masquelet therapy) suffering from a non-union older than 60 years treated between 01/01/2010 and 31/12/2016 in our institution were included into the current study. Bone consolidation was achieved in 91.9% after one-step and 76.9% after the Masquelet therapy. Analysis of age as a risk factor in the outcome of non-union therapy revealed no significant differences in patients treated with the one-step procedure according to the "diamond concept". On the contrary, age had a significant negative influence on the outcome of the Masquelet therapy (p = 0.027). Conclusion: Non-union therapy according to the "diamond concept" is an effective and reliable treatment option in elderly patients. According to findings of the current study, older adults suffering from an infected non-union benefit from a two-stage procedure, whereas in patients suffering from a non-infected non-union, a one-step surgical treatment is beneficial.